Altered acrylic acid concentrations in hard and soft corals exposed to deteriorating water conditions - Lori S.H. Westmoreland; Jennifer N. Niemuth; Hanna S. Gracz; Michael K. Stoskopf (Canadian Science Publishing, 2017)
A reliable marker of early coral response to environmental stressors can help guide decision-making to mitigate global coral reef decline by detecting problems before the development of clinically observable disease. We document the accumulation of acrylic acid in two divergent coral taxa, stony small polyp coral (Acropora sp.) and soft coral (Lobophytum sp.), in response to deteriorating water quality characterized by moderately increased ammonia (0.25 ppm) and phosphate (0.15 ppm) concentrations and decreased calcium (360 ppm) concentration, using nuclear magnetic resonance spectroscopy (NMR)-based metabolomic techniques. Changes in acrylic acid concentration in polyp tissues free of zooxanthellae suggest that acrylic acid could be a product of animal metabolism and not exclusively a metabolic by-product of the osmolyte dimethylsulfoniopropionate (DMSP) in marine algae or bacteria. Our findings build on previously documented depletions of acrylic acid in wild coral potentially correlated to temperature stress and provide additional insight into approaches to further characterize the nature of the metabolic accumulation of acrylic acid under controlled experimental conditions.